PENGARUH CAPITAL ADEQUACY RATIO, NON PERFORMING LOAN, LOAN TO DEPOSIT RATIO TERHADAP RETURN ON ASSET - Ambarawati, I Gusti Ayu Dwi; Abundanti, Nyoman (E-Jurnal Manajemen, 2018)
Bank performance can be measured with return on asset. Return on assets can be used to measure the effectiveness of a company in achieving profit by utilizing the assets owned. This study aims to determine the effect of capital adequacy ratio, non-performing loan, loan to deposit ratio to return on assets. This study was conducted at a banking company listed in Indonesia Stock Exchange (IDX) period 2014 - 2016. Samples determined by using purposive sampling technique and the number of selected samples is 34 banks. Data collection was done by non participant observation method. Data analysis technique used is multiple linear regression. The result of this research analysis shows that capital adequacy ratio have positive and significant effect to return on asset. Non performing loan has a negative and significant effect on return on asset. Loan to deposit ratio has a positive and significant effect on return on asset. Keywords: Return On Asset, Capital Adequacy Ratio, Non Performing Loan, Loan To Deposit Ratio.